Description of clean and healthy lifestyle behaviour implementation in MI Ma’arif Gandrungmanis Cilacap students during the pandemic time Covid-19 - Cahya Rahma Miftah; Sunarto Sunarto (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Clean and healthy living behaviour (PHBS) in elementary school (SD) children, in the age range of about 10 years, is often discussed because it is associated with active physical activity.Objective: To describe the developments in PHBS during the COVID-19 pandemic in elementary school childrenMethods: This study used a quantitative descriptive design with a survey method using a questionnaire to determine the description of PHBS implementation in 4th, 5th, and 6th-grade students of MI Ma’arif Gandrungmanis. The data was obtained by identifying students’ behaviour regarding PHBS towards health protocols during the Covid-19 pandemic in schools.Results: The results of this study show an overview of the PHBS of MI Ma’arif Gandrungmanis students during the Covid-19 pandemic with a very good category of 7.8%, good category of 28.4%, fairly good category of 37.1%, less good category of 20.7%, and not good category 6%.Conclusion: The PHBS in 4th, 5th, and 6th-grade of MI Ma’arif Gandrungmanis is mostly in the fairly good category with a percentage of 37.1%.